Facile synthesis of Pt-decorated Ir black as a bifunctional oxygen catalyst for oxygen reduction and evolution reactions. Issue 18 (26th April 2019) - Fang, Dahui; Tang, Xuejun; Yang, Limeng; Xu, Dongyan; Zhang, Hongjie; Sun, Shucheng; Shao, Zhigang; Yi, Baolian
Abstract : Ir black catalyzes the water reducing Pt 2+ to fabricate Pt@Ir as a bifunctional oxygen catalyst for both the ORR and OER. Abstract : Pt-Decorated Ir black (Pt@Ir) nanoparticles with two varying Pt mass fractions (Pt4 @Ir96 and Pt16 @Ir84 ) were generated by a facile method in water with the aid of Ir black. The Pt@Ir nanoparticles were investigated as a bifunctional oxygen catalysts for both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in acidic medium. Benefiting from the good dispersion of ultrafine Pt nanodots on the Ir black surface and the synergistic effect between the Pt and underlying Ir atoms, Pt@Ir nanoparticles have exhibited outstanding ORR activity and comparable OER performance in comparison with commercial Ir black. In particular, Pt16 @Ir84 shows an ORR mass activity of 2.6 times that of commercial Pt black and exhibits much better bifunctional performances than a mixture of Pt black and Ir black with a Ir/Pt mass ratio of 50/50 (Pt50 Ir50 ). Our work highlights the effectiveness of decorating Ir black with Pt nanodots to fabricate bifunctional oxygen catalysts.